Moralitas Iklan: Menghindarkan Keterjebakan Produsen dari Praktek Periklanan yang Kontra Produktif - Arif Hartono (Jurnal Siasat Bisnis, 2005)
An advertising is an important tool to unite producers and consumers in the communication media.  It is needed by both of producers and consumers, but in different functions. Producers need an advertising to promote their products, and consumers need it to get more information about products before making a buying decision. Because of that, producers must give the true information by presenting right method (not tricky, bombastic, lie, etc.). Producers must be carefull in the advertising to make consumer sympathetic. If consumers feel dissapointed about it, they will leave a producer and move to other producer.           Key Words : Iklan, moralitas, efektivitas, kontra produktif